Tinjauan Literature: Mengeksplorasi Faktor-Faktor yang Memotivasi Generasi Z untuk Bekerja - Purnama Dewi's, Ari; Rahayu Indrawati, Komang (Jurnal Manajemen dan Organisasi, 2025)
Generation Z has increasingly entered the workforce and is projected to succeed Generations X and Y in the organizational landscape. Motivation is recognized as a critical factor influencing their work performance. However, existing research indicates that Generation Z exhibits lower levels of engagement motivation than preceding generations, which contributes to difficulties sustaining long-term employment. This phenomenon warrants closer examination, given the strategic importance of Generation Z as the future workforce. Accordingly, this study aims to identify and analyze the factors influencing work motivation among Generation Z through a systematic literature review (SLR), following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework as the methodological foundation. Literature was sourced from Google Scholar and Crossref using Harzing’s Publish or Perish software with the keywords "Work Motivation," "Gen Z Employee Work Motivation," and "Gen Z Work Motivation." Ten relevant articles were selected for in-depth analysis following a screening and exclusion process. The results of this study indicate that Generation Z’s work motivation is driven by meaningful achievement through appreciation, affiliation manifested in flexible, supportive, and participative work environments, and interestingly, social recognition is no longer a primary priority as it was for previous generations. These findings are expected to support organizations in designing relevant human resource policies to enhance Generation Z employees' productivity.